Proceedings of the 5th International Asia Conference on Industrial Engineering and Management Innovation (IEMI2014) - Qi, Ershi; Su, Qin.; Shen, Jiang; Wu, Feng.; Dou, Runliang; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2015)
The 5th International Asia Conference on Industrial Engineering and Management Innovation is sponsored by the Chinese Industrial Engineering Institution and organized by Xi$1 (Ban Jiaotong University. The conference aims to share and disseminate information on the most recent and relevant researches, theories and practices in industrial and system engineering to promote their development and application in university and enterprises.s
A Fuzzy Petri nets/ANP Evaluation Model on Business Process Reengineering Implementation -- Recent Advances in Concurrent Engineering Modeling -- The Construction of the Streamline Curve and Surface -- Applying Combined Hierarchical Analysis and Extension Methods for Siting Senior Day-Care Center -- A Prospect Theory Based Approach to Heterogeneous Multiple Attribute Group Decision Making -- ME-OWA based DEMATEL-ISM Accident Causation Analysis of Complex System -- The Optimal Consignment Policy for the Retailer Facing Multiple Manufacturers -- Emergency Decision-supporting System Based on Multi-Agents Negotiation -- Study on Consumers$1 (BChannel Choice Behavior Based on Fishbein$1 (Bs Model of Reasoned Action -- Research on Credibility Support Mechanism of Manufacturing Cloud Service Based on Classified QoS.s
Keywords: Economics; Information Systems; Industrial engineering; Economics/Management Science; Innovation/Technology Management; Industrial and Production Engineering; Management of Computing and Information Systems; Control